Linkages between Electricity Consumption and Economic Growth: Evidences from South Asian Economies - Dhungel, Kamal Raj (Hydro Nepal: Journal of Water, Energy and Environment, 2017)
Researchers have options to choose the model to assess the exact relationship between electricity consumption and economic activity. One can use the model based either in demand side or in supply side. This paper considers electricity as an essential factor of production. Thus it uses the demand side model to reexamine the association and determine the causality between the variables electricity consumption (EC) and gross domestic product (GDP) of five south Asian countries during the period 2000-2011 AD. A panel unit root test, panel co-integration test are used to determine the long run equilibrium. Fully modified ordinary least square method was applied to estimate the panel electricity elasticity coefficient. Granger causality based on Vector Auto Regression model was then applied to determine the direction of causality. The data are found stationary at first difference but are found non-stationary at their level. Co-integration test confirmed the long run relationship or equilibrium between the variables EC and GDP. The electricity elasticity coefficient (EEC) is 1.31. It reveals that a 1% increase in electricity consumption would lead to increase the GDP by 1.31% indicating a highly responsive electricity demand. In the spontaneous process of economic development of south Asian countries, there is a significant impact of EC on GDP. The value of EEC is self-spoken. A large change in GDP would be expected from a small change in EC. It has a big implication of bringing rapid economic progress within a short span of time and any shortage of electric energy would retard economic progress. Electricity consumption is found to Granger cause GDP. This unidirectional causality running from electricity consumption to GDP has important policy implication-electricity consumption leads economic growth which has two policy implications. One, reduction of electricity consumption through bringing domestic energy prices in line with market prices would lead to fall in GDP or employment. Two, electricity consumption bears the burden of short run adjustment to reestablish the long run equilibrium. HYDRO Nepal Journal Journal of Water Energy and Environment Issue: 20 Page: 18-22